2019
DOI: 10.1159/000499927
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural Adaptation and Validation of the Voice Handicap Index-10 into the Serbian Language

Abstract: Background: The Voice Handicap Index-10 (VHI-10) is used in clinics because of its validity and ease of use by patients. Objectives: The aim of this paper was to evaluate the internal consistency, reliability, and clinical validity of the Serbian version of the VHI-10. Method: In this cross-sectional study, we translated the original English version of the VHI-10 into Serbian, after which it was back-translated into English. The Serbian version of the VHI-10 was completed by 161 patients with voice disorders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our findings confirm the validity of the Montenegrin VHI-10 version in line with normative values laid down by Arffa et al ( 31 ) and is, in fact, well above its cut-off level (>11). Our results are also in agreement with findings reported for the original English version ( 18 ) and subsequent translations into, Arabic, Brazilian Portuguese, Chinese, Hebrew, Serbian, and Spanish ( 19 , 20 , 21 , 22 , 23 , 26 ) inasmuch as they are good instruments to distinguish between normal and abnormal voice conditions. Furthermore, the highest mean VHI-10 score in our study was found in patients with neurological voice disorders, which confirms earlier reports ( 20 , 21 , 27 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings confirm the validity of the Montenegrin VHI-10 version in line with normative values laid down by Arffa et al ( 31 ) and is, in fact, well above its cut-off level (>11). Our results are also in agreement with findings reported for the original English version ( 18 ) and subsequent translations into, Arabic, Brazilian Portuguese, Chinese, Hebrew, Serbian, and Spanish ( 19 , 20 , 21 , 22 , 23 , 26 ) inasmuch as they are good instruments to distinguish between normal and abnormal voice conditions. Furthermore, the highest mean VHI-10 score in our study was found in patients with neurological voice disorders, which confirms earlier reports ( 20 , 21 , 27 ).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the highest mean VHI-10 score in our study was found in patients with neurological voice disorders, which confirms earlier reports ( 20 , 21 , 27 ). The strong internal consistency and excellent test-retest reliability of the Montenegrin VHI-10 also put it side by side with the Danish, Hebrew, Italian, and Serbian versions ( 21 , 24 , 26 , 27 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The VHI-10 has shown a good correlation to the results of the VHI-30 and has been thoroughly validated by internal consistency, reliability, and test-retest reliability tests [12,13]. In addition, normative values [14] and minimal important differences [15] has been established for the questionnaire and it now exists in multiple languages [16][17][18]. Thus, the VHI-10 is a well-suited clinical tool for patient self-evaluation of the severity of a voice disorder.…”
Section: Introductionmentioning
confidence: 99%